Analysis and Design of Damping Resistor for Mitigating Surge Voltage and Oscillation in Flyback Converter - Sunggyu Jin; Jongwon Choi (IEEE Access)
An analytical method is presented for designing damping resistance to minimize surge voltage in a flyback converter with a dissipative snubber. It is based on given snubber capacitance and resistance. Flyback converters have an inherent issue with unwanted surge voltage at the main FET due to leakage inductance of the transformer. To handle it, a dissipative snubber has been widely used for mitigating the surge voltage and it can be efficiently adjusted according to the parameters of the R-RCD snubber. To derive a damping resistance with minimum surge voltage, an equivalent circuit was developed to address RCD snubber with a damping resistor, and the drain-source voltage response was obtained. Furthermore, the snubber loss during the discharge interval in the snubber capacitor was calculated. The analysis involved examining the relationship between the surge voltage at the drain-source voltage and the loss during discharge. Using the trade-off relationships, a new cost function was proposed to balance its surge voltage and efficiency. The optimal damping resistance and snubber capacitance were obtained based on the cost function. The analysis is demonstrated by experimental results using a 54W prototype flyback converter.